EAOnto: a heavyweight ontology for supporting e-assessment generation - Romero, Lucila (2012)
Different approaches that use ontology as a tool for generating, organizing and personalizing e-learning content can be found in literature. In the context of e-assessment, the notion of ontology has been used for different purposes. One of them is the use of ontologies as a mean of providing a structure to guide the automated design of assessments. Despite of the effort done in this direction, there is still a lot of work to be done since the most of the approaches have proposed lightweight ontologies that model a part of the assessment domain without considering pedagogical aspects. This paper presents a heavyweight ontology, called EAOnto, that conceptualizes the e-assessment domain including a set of rules representing pedagogical principles that are worth to follow. In addition, an empirical evaluation is discussed.